Lattice gas simulations of dynamical geometry in two dimensions. - Klales, Anna.; Cianci, Donato.; Needell, Zachary.; Meyer, David A.; Love, Peter J. (Tufts University. Tisch Library., 2018)
We present a hydrodynamic lattice gas model for two-dimensional flows on curved surfaces with dynamical geometry. This model is an extension to two dimensions of the dynamical geometry lattice gas model previously studied in one dimension. We expand upon a variation of the two-dimensional flat space Frisch-Hasslacher-Pomeau (FHP) model created by Frisch et al. [Phys. Rev. Lett. 56, 1505 (1986)] and independently by Wolfram, and modified by Boghosian et al. [Philos. Trans. R. Soc. London, Ser. A 360, 333 (2002)]. We define a hydrodynamic lattice gas model on an arbitrary triangulation whose flat space limit is the FHP model. Rules that change the geometry are constructed using the Pachner moves, which alter the triangulation but not the topology. We present results on the growth of the number of triangles as a function of time. Simulations show that the number of triangles grows with time as t^1/3, in agreement with a mean-field prediction. We also present preliminary results on the distribution of curvature for a typical triangulation in these simulations.